Redesain Susunan Keanggotaan Dewan Perwakilan Daerah dalam Sistem Ketatanegaraan Indonesia (International Forum of Researchers and Lecturers, 2025)
The Regional Representatif Council (DPD) is an institution that was born as a result of amendments to the 1945 Constitution from 1999 to 2002. This institution existed as a response to the centralization of government in the new order which caused various upheavals in the regions. Apart from that, the DPD is also expected to be able to create a check and balance mechanism between legislative institutions (DPR and MPR) as well as realizing the DPD as a regional representation. The current authority and membership of the DPD is not sufficient to create a check and balance mechanism for both the DPD and DPR and the DPD in the MPR forum. Apart form that, party sympathizers and domicile requirements that are too loose mean that the DPD as regional representation has not been realized optimally. Designing the authority and membership by maximizing legislative functions and increasing the number of members can be create checks and balances between legislative institutions. Apart from that, a new design of the DPD nomination requirements is also needed, by prohibiting nominations of political party sympathizers and narrowing the domicile requirements to realize the DPD as a genuine regional representation.